What Ails Kerala's Economy: A Sectoral Exploration - P D JEROMI (Economic and Political Weekly April 19, 2003, 2003)
The `Kerala model' of development has been facing a serious crisis due to low growth, high cost, low productivity, low investment and low employment in the state economy. This paper analyses the performance of major sectors of the state economy, such as agriculture, industry and the financial sector, during the past two decades and brings out the problems they confront. The paper highlights the lack of a development strategy in Kerala for growth and employment generation.